2012
DOI: 10.1258/shorts.2012.011173
|View full text |Cite
|
Sign up to set email alerts
|

Views of Patients about Sickle Cell Disease Management in Primary Care: A Questionnaire-Based Pilot Study

Abstract: ObjectivesTo determine how patients with sickle cell disease (SCD) perceive the quality of care that they receive from their primary healthcare providers.DesignA questionnaire-based pilot study was used to elicit the views of patients about the quality of care they have been receiving from their primary healthcare providers and what they thought was the role of primary care in SCD management.SettingSickle Cell Society and Sickle Cell and Thalassaemia Centre, in the London Borough of Brent.ParticipantsOne hundr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 15 publications
0
13
0
1
Order By: Relevance
“…Furthermore, these patients may not be aware that PHC activities are aimed at prevention, promotion of health, and continuous care, and may even have sought the service previously and not obtained an effective solution to their problem at that time. 1–3,6 …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, these patients may not be aware that PHC activities are aimed at prevention, promotion of health, and continuous care, and may even have sought the service previously and not obtained an effective solution to their problem at that time. 1–3,6 …”
Section: Discussionmentioning
confidence: 99%
“…Also, the age and comorbidity breakdowns were similar between the least and most deprived groups (data not shown). Targeted intervention programs 29,30 that concentrate on a small number of 'high-risk' patients, such as improving access to appropriate care or adherence to medication protocols 31,32 provide genuine opportunities to prevent a large number of recurrent hospitalizations. Some readmissions may also be prevented through policy initiatives such as the development and implementation of local enhanced services for people with SCD.…”
Section: What This Study Addsmentioning
confidence: 99%
“…11 One study assessing the views of patients with SCD showed that patients and carers often bypass their general practitioner for acute problems and attend directly at accident and emergency (A&E) suggesting better primary care interventions could reduce emergency admissions. 20,21 One study looked at 145 general practices in the East Midlands and showed that as the proportion of patients able to consult their primary care physician increased, emergency admission rates decreased. 22 The rate is given by the number of admissions in emergency and elective over the number of population in the PCT for 2011.…”
mentioning
confidence: 99%